Chinese Herbal Cardiotonic Pill Stabilizes Vulnerable Plaques in Rabbits by Decreasing the Expression of Adhesion Molecules. Issue 3 (September 2016) - Chen, Liang; Li, Xiaonan; Li, Changjiang; Rong, Yuanyuan; Xiao, Yawei; Xu, Xinsheng; Yao, Guihua; Jiang, Guihua; Zhang, Mei
Abstract : Abstract: The cardiotonic pill (CP), consisting of a mixture of Radix Salviae Miltiorrhizae, Radix Notoginseng, and Borneolum Syntheticum, has been widely used in the prevention and treatment of cardiovascular disease. Adhesion molecules, including intercellular cell adhesion molecule-1 and vascular cell adhesion molecule-1, are involved in the development of vulnerable plaque. We investigated the effect of the CP in a rabbit model of vulnerable plaque established by local transfection with p53 gene. Compared with the control group, rabbits with vulnerable plaque showed a significantly lower intima-media thickness and plaque burden after CP treatment for 12 weeks. Moreover, the reduction in rate of plaque rupture and vulnerability index was similar. On enzyme-linked immunosorbent assay, real-time polymerase chain reaction, and immunohistochemistry analysis, the expression of intercellular cell adhesion molecule-1 and vascular cell adhesion molecule-1 was inhibited with CP treatment. CP treatment could postpone atherosclerotic plaque development and stabilize vulnerable plaque by inhibiting the expression of adhesion molecules in treatment of cardiovascular disease.